Communication lapses to combating COVID-19 pandemic: Evaluating Ghana's COVID-19 campaign. (1st June 2021) - Nyarko, Jacob; Serwornoo, Michael Yao Wodui; Azanu, Benedine
COVID-19 is described as 'novel' largely because the virus has rarely been studied. Without any vaccine, the key to containing the virus was the timely delivery of educative public health information to people. With a population of 29 million composed of small urban segments, Ghana has enormous rural enclaves where most of her citizens live. This study seeks to explore the nature of Ghana's COVID-19 campaign, focusing on the communication strategies and the extent to which indigenous communication tools (ICTs) have been employed. Relying on document analysis, Ghana's COVID-19 campaign rarely deployed ICTs but rather paid lip service to the country's indigenous resources in public addresses to the nation. It also found that the fight against the virus metamorphosed into political campaigns making WHO's vital information subservient to images of political figures and political iconography in general. We argue that the nature of the campaign created generalized awareness of the pandemic, but did less to educate the masses on the WHO preventive protocols.